Identification of the Minimal Disease Activity Domains Achieved Based on Different Treatments in Psoriatic Arthritis - Silvia Scriffignano; Fabio Massimo Perrotta; Paola Conigliaro; Mario Ferraioli; Paola Triggianese; Maria Sole Chimenti; Ennio Lubrano (Rheumatology and Therapy, 2023)
Abstract Introduction The aim of this work is to characterize which Minimal Disease Activity (MDA) domains are mainly achieved, based on different treatments, in psoriatic arthritis (PsA) patients. Moreover, the association between MDA achievement and the different treatment groups was assessed. Methods We conducted a cross-sectional analysis of two longitudinal PsA groups. Inclusion criteria were: age ≥ 18 years, PsA diagnosis, stable treatment for at least 6 months. Patients were grouped depending on the therapy: group 1: Non-Steroidal Anti-Inflammatory Drugs (NSAIDs)/cyclooxygenase 2 inhibitors (COX2i)/steroids, group 2: conventional synthetic Disease-Modifying Anti-Rheumatic Drugs (csDMARDs), group 3: Tumor Necrosis Factor α  inhibitors (TNFi), group 4: interleukin inhibitors (IL)12-23i or IL-23i, group 5: IL-17i, group 6: phosphodiesterase 4 inhibitors (PD4i). For each group, the achieved domains based on therapy were assessed. Multivariate logistic regression analysis was performed to assess the association between the treatment groups and the MDA achievement. Results A total of 220 patients were enrolled, and MDA was achieved in 45.8% of them. In all treatment groups, the first MDA domains achieved were: body surface area ≤ 3, swollen joint count ≤ 1 and Leeds Enthesitis Index ≤ 1, while MDA domains less frequently achieved were Patient Global Assessment (PtgA) ≤ 2 cm and pain on visual analogue scale ≤ 1.5 cm. The logistic regression analysis showed higher odds ratios for the achievement of the MDA in those patients in groups 3 and 4. Conclusions In each treatment group, MDA domains less frequently achieved were PtGA and pain, suggesting that “patient-driven domains” are still an unmet need. Due to the study design and the low number of patients in some groups, it is not possible to clearly define which MDA domain was achieved or not based on treatment; however, it seems that some differences could be present. If larger and prospective studies confirm our preliminary results, we could move toward a personalized/domain treatment approach in PsA.